Generation of Electron Acoustic Waves in the Topside Ionosphere From Coupling With Kinetic Alfven Waves: A New Electron Energization Mechanism. Issue 11 (13th June 2018) - Shi, Run; Ni, Binbin; Summers, Danny; Liu, Huixin; Yoshikawa, Akimasa; Zhang, Beichen
Abstract: Results from a new drift kinetic model in the topside ionosphere capture the mode conversion from kinetic Alfven waves to electron acoustic waves. When the kinetic Alfven waves propagate into the transition region, where the electron density of ionospheric origin becomes comparable to that of magnetospheric origin, the steep temperature gradient leads to the mode conversion. The electron acoustic waves are short‐lived by dissipating their energy into the electron energization, thus revealing a new type of electron acceleration in the topside ionosphere. Plain Language Summary: We investigate the electron acceleration by Alfven waves in the topside ionosphere using a new kinetic model and capture for the first time the mode conversion from kinetic Alfven waves to electron acoustic waves. A new type of electron acceleration is shown to contribute to electron energization in the auroral region. Our new findings provide important insights into the mechanisms of auroral electron acceleration, which is critical in understanding wave particle interaction in the auroral acceleration region and magnetosphere‐ionosphere coupling processes. Key Points: A new kinetic model is developed to simulate the wave‐particle interaction in the topside ionosphere Mode conversion from kinetic Alfven waves to electron acoustic waves is revealed in the transition region A new type of electron acceleration is shown to contribute to electron energization in the formation of the discrete aurora